SPE Middle East Oil and Gas Show and Conference 2019
DOI: 10.2118/194842-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Weighting Materials for Ultra-High Density Oil-Based Drilling Fluids in Ultra-HPHT Wellbore Applications

Abstract: Global energy demand has driven the petroleum industry to develop hydrocarbon resources from extremely harsh formations which contain ultra-high pressure and temperature (HPHT) reservoirs. Ultra-high density drilling fluids are critical to successful drilling and completion practices in all of these wells. In this paper, potential weighting materials were systematically evaluated and screened to accomplish an ultra-high density oil-based drilling fluid system (19.62 to 22.12lb/gal) aimed to utilize in ultra HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…The key features of Mn 3 O 4 were exploited by combining with ilmenite to get ultrahigh-density drilling fluid with a density of 22.12 lb/gal. The testing of a Mn 3 O 4 and ilmenite mixture under drastic field conditions of 410 °F and 300 psi proved their stability . Later on, another research group did a similar study with Mn 3 O 4 and ilmenite and supported the outcomes of previous research outcomes .…”
Section: Oilfield Applications Of High-density Brinesupporting
confidence: 66%
See 1 more Smart Citation
“…The key features of Mn 3 O 4 were exploited by combining with ilmenite to get ultrahigh-density drilling fluid with a density of 22.12 lb/gal. The testing of a Mn 3 O 4 and ilmenite mixture under drastic field conditions of 410 °F and 300 psi proved their stability . Later on, another research group did a similar study with Mn 3 O 4 and ilmenite and supported the outcomes of previous research outcomes .…”
Section: Oilfield Applications Of High-density Brinesupporting
confidence: 66%
“…The testing of a Mn 3 O 4 and ilmenite mixture under drastic field conditions of 410 °F and 300 psi proved their stability. 116 Later on, another research group did a similar study with Mn 3 O 4 and ilmenite and supported the outcomes of previous research outcomes. 117 The comparison of ultrafine barite, Mn 3 O 4 , barite, and ilmenite as weighing agents proved the most effective role of ilmenite in drilling fluid rheology and fluid loss control as shown in Figure 5.…”
Section: High-density Brines As Drilling Fluidssupporting
confidence: 64%
“…Many materials were used as weighting agents over the years, and researchers are still looking for new materials and ways to improve the existing ones. Examples of common weighting materials include barite, calcium carbonate, ilmenite, hematite, manganese tetroxide (Micromax), galena, stibnite, and potash. One potential method to improve the weighting material performance is by reducing its particle size; this introduced more options such as micronized barite, micronized ilmenite, and micronized manganese tetroxide as weighting materials. Furthermore, other researchers used a mixture of several weighting materials with the aim of mitigating drilling instability issues such as barite sagging and of improving the drilling mud properties. , Also, nanoparticles were investigated as weighting agents by several studies that showed a general improvement in the drilling fluid properties. , Accordingly, selecting the right weighting material is not a trivial task and it depends on many factors including the cost, the required properties (i.e., density), and its solubility in conventional filter cake removal treatments since it affects approximately 70–80% of the filter cake structure …”
Section: Introductionmentioning
confidence: 99%
“…8−10 Commonly used weighting materials are calcium carbonate, barium sulfate or barite, hematite, manganese tetroxide, and ilmenite. 11,12 During the drilling operation, the drilling fluids impair the permeability of the formation upon their invasion into the formation. The invaded particles block the pore throat and lead to a loss of permeability of the produced formation by building a filter cake on the wall of the permeable formation.…”
Section: Introductionmentioning
confidence: 99%